Petroleum emplacement inhibits quartz cementation and feldspar dissolution in a deeply buried sandstone. (August 2020) - Xia, Changyou; Wilkinson, Mark; Haszeldine, Stuart
Abstract: Whether the emplacement of petroleum in sandstone reservoirs can preserve porosity during burial remains controversial. In the Kessog Field, UK Central North Sea, average porosities of the crestal sections of the fluvial-deltaic Pentland Formation reservoir can exceed 25% despite burial to 4 km or more. The predicted porosity for the reservoir at this depth is only around 14% based on regional data. Oil saturation data, thin-section point counts, grain-size and sorting measurements, reservoir pressure, and SEM images were combined to analyze the cause of the high reservoir porosity. Petroleum emplacement preventing cementation is the most likely mechanism for porosity preservation. Facies variation is not responsible, as the high-porosity sandstones from the crestal well are, in terms of average grain-size (fine-grained) and sorting coefficient (moderately well-sorted), nearly the same as the lower porosity sandstones from the flanks of the field (average porosity 13–15%). Other potential porosity-preservation mechanisms, such as overpressure, grain-coats and feldspar dissolution can be discounted. The sandstones with high oil saturations are characterized by: 1) most porosity being primary as opposed to secondary; 2) there being 2–5% less quartz cement than in the water-saturated sandstones; 3) there being 2–3% more K-feldspar and 2–6% less kaolin than the water-saturated counterparts. This study demonstrates that petroleum emplacement can effectively inhibit quartz cementation and K-feldspar transformation to kaolin in sandstone reservoirs. Highlights: Early oil charge is interpreted to be the cause of the high-porosity Kessog Sandstone. Oil-saturated sandstones may contain 10–15% more porosity than normal sandstones. Oil charge may also retard the process of K-feldspar dissolution to form kaolin.